1983
DOI: 10.1002/ajmg.1320150414
|View full text |Cite
|
Sign up to set email alerts
|

Screening of mentally retarded males for macro‐orchidism and the fragile X chromosome

Abstract: Four hundred forty-four male residents of a state mental retardation institution were screened for macro-orchidism. Twenty-six white males (8.3%) and two black males (1.5%) had marked macro-orchidism (greater than 34 ml). Seven of 17 whites tested for the fragile X were positive; the one black tested was negative. Thus, a minimum of 7/26 or 27% (whites) are fragile X positive indicating potential population variability, also evident from previous reports. Concurrent testing of institutionalized brother pairs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

1984
1984
1994
1994

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…In the authors' preliminary study, macro-orchidism was found to be present in 20" 8% of institutionalized males (Pozsonyi et al, 1981). This finding has since been confirmed by Brondum-Nielsen et al (1983) and Howard-Peebles & Finley (1983) who reported that the incidence of macro-orchidism among mentally retarded males was 29% and 20%, respectively. Howard-Peebles & Finley (1983) and Primrose (1984) found testes exceeding 34-35 ml in 8-3% and 12-9% (after exclusion of Down's syndrome patients) of retarded males respectively.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the authors' preliminary study, macro-orchidism was found to be present in 20" 8% of institutionalized males (Pozsonyi et al, 1981). This finding has since been confirmed by Brondum-Nielsen et al (1983) and Howard-Peebles & Finley (1983) who reported that the incidence of macro-orchidism among mentally retarded males was 29% and 20%, respectively. Howard-Peebles & Finley (1983) and Primrose (1984) found testes exceeding 34-35 ml in 8-3% and 12-9% (after exclusion of Down's syndrome patients) of retarded males respectively.…”
Section: Discussionsupporting
confidence: 64%
“…Reported frequencies for the fra(X) syndrome among institutionalized males have varied greatly as a result of different selection criteria (IQ levels, physical phenotype, family history of XLMR) (Venter & Op't, 1982;Carpenter et al, 1982;Sutherland, 1982;Blomquist et al, 1982Blomquist et al, , 1983Jacobs et al, 1983;Froster-Iskenius et al, 1983;Primrose et al, 1986). The fra (X) frequency has been shown to increase dramatically among MR males selected on the basis of increasing testicular size (Brondum-Nielsen et al, 1982;Shapiro et al, 1983;Howard-Peebles & Finley, 1983). The overall consensus of these studies ranks the fra(X) syndrome second to Down's syndrome as a major cause of mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Significant FMR-1 protein expression may be responsible for higher cognitive functioning in the 2 males with unmethylated INTRODUCTION In the early years of fragile X (fra(X)) male identification; it was the severely affected individuals who came to medical attention, and most reports defined all fra(X) males as mentally retarded [Martin and Bell, 1943;Turner et al, 1980;Hagerman et al, 19831. Institutional studies furthered the concept that fra(X) males are retarded since almost all patients in an institution for the developmentally disabled are retarded. Approximately 2%-10% of institutionalized patients were found to be fra(X) positive by cytogenetic analysis and these individuals represented the severe end of the fra(X) spectrum [Carpenter et al, 1982;Froster-Iskenius et al, 1983;Howard-Peebles and Finley, 1983;Primrose et al, 1986;Hagerman et al, 19881. In 1981, Daker et al [1981 presented a surprising report of a normal man who demonstrated the fra(X) chromosome.…”
mentioning
confidence: 99%
“…The observation of an excessive number of mildly retarded boys with large testes suggests that there may be an allelic mutation which gives rise to x-linked mental retardation and large testes, without the fragile site. Jennings et al (1980) found one such family, and other cases have been reported by Fishburn et al (1983) andHoward-Peebles andFinley (1983). When the gene associated with mental retardation is identified in patients with the fragile x syndrome, it will be of great interest to look again at the boys with macro-orchidism and no fragile x to see whether they have a mutation at the same site.…”
Section: Discussionmentioning
confidence: 99%
“…Jennings et al (1980) found one such family, and other cases have been reported by Fishburn et al (1983) andHoward-Peebles andFinley (1983). Jennings et al (1980) found one such family, and other cases have been reported by Fishburn et al (1983) andHoward-Peebles andFinley (1983).…”
Section: Schools Inmentioning
confidence: 99%